Perancangan Gedung MICE KAI Corporate University Di Bandung Dengan Pendekatan Arsitektur Biomimikri - Yanti, Sinta Dwi (TERAKOTA : Jurnal Poster Arsitektur, Interior dan Rancang Kota, 2024)
The city of Bandung has experienced developments in its city infrastructure over time. There is quite rapid development in various things, for example in the categories of business, industrial, political and cultural centers. With the existing developments, there has been a lot of activity or social activity that occurs in this city. Presence of MICE, the need for meeting places is increasing over time. We need to invest in cities that are starting to develop MICE. This emerged as a rejection of modern architectural principles which do not pay attention to architecture's relationship with things that are considered trivial and are only limited to fulfilling the functions of its users, causing a decline in architectural value. Metabolism brings a vision to bring about changes in the appearance of architecture, especially architecture that is capable of changing, developing and responding to environmental conditions. Building an object is not just about building a building, but also involves how to build it for everyone in a way that is comfortable and does not damage the existing environment. The concept that suits the existing problem is the concept of biomimicry. In the book entitled biomimicry, Biomimicry is a concept where nature plays the main role or model. The architectural design of the planned building will create a building that is in harmony and blends with nature.